Photoinhibition in cork-oak leaves under stress: influence of the bark-stripping on the chlorophyll fluorescence emission inQuercus suber L. - Werner, Christiane; Correia, O. (Trees-Structure and Function, 1996)
Quercus suber is the primary source for industrial cork and becomes bark-stripped every 9 – 10 years. Recurring cork extraction is a major stress factor and the large water loss from the stripped trunk surface may affect the water balance and tree productivity. To evaluate the effect of bark-stripping, fluorescence emission and stomatal conductance of leaves were determined in groups of barkstripped and control trees. Fv/Fm ratio was found to be significantly lower in bark-stripped trees indicating a reduced photosynthetic efficiency of PSII. Photosynthesis was not found to be stomata limited. The reduction in Fv/Fm resulted from a decline in maximum and variable fluorescence while the initial fluorescence of the darkadapted state (Fo) remained constant. A general decline in photosynthetic efficiency of PSII was found in all trees during the summer, probably reflecting the prolonged environmental stresses during a hot and dry season. Additional stress caused by the bark-stripping seems to enhance the susceptibility to photoinhibition of the trees.
Keywords: bark-stripping; fluorescence emission; Quercus Suber L; water relations

Effects of bark-stripping on the water relations of Quercus suber L - Correia, O. A.; Oliveira, G.; Martins-Loução, M. A.; Catarino, F. M. (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations